Effect of TiB2 particles on microstructure and mechanical properties of B4C–TiB2 ceramics prepared by hot pressing. Issue 3 (1st February 2023) - Guo, Wenchao; He, Qianglong; Wang, Aiyang; Tian, Tian; Liu, Chun; Hu, Lanxin; Wang, Weimin; Wang, Hao; Fu, Zhengyi
Abstract: B4 C-20 wt% TiB2 ceramics were fabricated by hot pressing B4 C and ball-milled TiB2 powder mixtures. The effects of the TiB2 particle size on the microstructure and mechanical properties were investigated. The results showed that the TiB2 particle size played an important role in the mechanical properties of the B4 C–TiB2 ceramics. In addition, SiO2 introduced by ball milling was beneficial for densification but detrimental to the mechanical properties of the B4 C–TiB2 ceramics. The typical values of relative density, hardness, flexural strength, and fracture toughness of the ceramics were 99.20%, 35.22 GPa, 765 MPa, and 7.69 MPa m 1/2, respectively. The toughening mechanisms of the B4 C–TiB2 ceramics were explained by crack deflection and crack branching. In this study, the effects of high pressure and temperature caused liquefying SiO2 to migrate to the surface of B4 C–TiB2 and react with diffused carbon source in the graphite foil to form a 30 μm thick SiC layered structure, which improved the high-temperature oxidation resistance of the material. The unique SiC layered structure overcame the insufficient oxidation resistance of B4 C and TiB2, thereby improving the oxidation resistance of the ceramics under high-temperature service conditions.